The Effect of Work–Life Integration and Work Initiative on Elementary School Teachers’ Performance with Job Satisfaction as a Mediating Variable - Fahriansyah, Fahriansyah; Siswanto, Romi; Kadarisman, Kadarisman; Mudayat, Mudayat (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze the effect of Work–Life Integration (WLI) and work initiative on the performance of elementary school teachers, with job satisfaction serving as a mediating variable. Employing an explanatory quantitative approach, the study used a survey method involving 240 elementary school teachers in West Kalimantan. Data were collected using a five-point Likert-scale questionnaire and analyzed through Structural Equation Modeling using PLS-SEM (version 4). The results indicate that WLI has a positive and significant effect on job satisfaction but does not have a significant direct effect on teachers’ performance. In contrast, work initiative exerts a positive and significant effect on both job satisfaction and teachers’ performance. Furthermore, job satisfaction is found to have a positive and significant effect on teachers’ performance, fully mediating the relationship between WLI and performance and partially mediating the relationship between work initiative and performance. These findings strengthen Boundary Theory, Proactive Behavior Theory, Herzberg’s Motivation Theory, and Human Capital Theory. From a practical perspective, the study highlights that improving teachers’ performance requires supportive school policies that foster healthy work–life integration and promote a sustainable culture of work initiative.